2017
DOI: 10.1080/23302674.2017.1315194
|View full text |Cite
|
Sign up to set email alerts
|

Integrated maintenance–quality policy taking into account the economical impact of reworking activities

Abstract: In this paper, we study integrated strategies joining maintenance and quality. We consider an imperfect manufacturing system composed of a single machine subject to an increasing random failure rate and producing conforming (first and second choice) and non conforming items. In order to decrease the failure rate and its impact on teh quality of output products, a preventive maintenance (PM) policy, block type, with minimal reapair is applied. Indeed, two different strategies are developed: The first strategy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Nevertheless, both of these activities mentioned above (operation and maintenance) are necessary and closely related not only to each other but also to other business processes, such as quality, logistics, SHE (Safety, Health, Environment), etc., as indicated below: [11] Integrated strategies joining maintenance and quality. [12] Spare parts management as a function of maintenance management that aims to support maintenance activities, providing real-time information on the available quantities of each spare part and adopting the inventory policies that ensure their availability when required, minimizing costs.…”
Section: Terminologymentioning
confidence: 99%
“…Nevertheless, both of these activities mentioned above (operation and maintenance) are necessary and closely related not only to each other but also to other business processes, such as quality, logistics, SHE (Safety, Health, Environment), etc., as indicated below: [11] Integrated strategies joining maintenance and quality. [12] Spare parts management as a function of maintenance management that aims to support maintenance activities, providing real-time information on the available quantities of each spare part and adopting the inventory policies that ensure their availability when required, minimizing costs.…”
Section: Terminologymentioning
confidence: 99%
“…Quality is increasingly becoming the key for enterprises to win the competition. Gouiaa-Mtibaa et al 13 found that quality characteristics of products fluctuate during the manufacturing process. The issue of integrating production and quality control received wide attention.…”
Section: Introductionmentioning
confidence: 99%